STUDY ON THE FENTON REACTION FOR DEGRADATION OF REMAZOL RED B IN TEXTILE WASTE INDUSTRY - Henry Setiyanto (Universitas Jenderal Soedirman, 2016)
Remazol Red B is a reactive dye that is often used in the textile industry. The dye can cause serious problems in the environmental / water because it is difficult to be degraded by microorganisms. Decolorization of reactive azo dyes (Remazol Red B) before being discharged into the environment is an important aspect in creating technology (method) that are environmentally friendly. The method chosen for this decolorization is Advanced Oxidation Process (AOP) using the Fenton reaction. The optimum conditions for this reaction is 25 mg/L H2O2 and 1.25 mg/L of Fe2+ to Remazol Red B with initial concentration at 83 mg/L ( with ratio [H2O2]/[Fe2+] = 20). The optimum conditions of this reaction were obtained at pH 3 and temperature of 27 0C, with decolorization efficiency up to 100% for a reaction time of 60 minutes. The kinetic model of dye decoloritation follow the second order reaction. Some of the metal ions were added i.e. Cu2+, Pb2+ and Zn2+ , given no significant impact on the degradation performed.